2020
DOI: 10.3390/nu12041118
|View full text |Cite
|
Sign up to set email alerts
|

Lactic Acid Fermentation of Cereals and Pseudocereals: Ancient Nutritional Biotechnologies with Modern Applications

Abstract: Grains are a substantial source of macronutrients and energy for humans. Lactic acid (LA) fermentation is the oldest and most popular way to improve the functionality, nutritional value, taste, appearance and safety of cereal foods and reduce the energy required for cooking. This literature review discusses lactic acid fermentation of the most commonly used cereals and pseudocereals by examination of the microbiological and biochemical fundamentals of the process. The study provides a critical overview of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 161 publications
4
57
1
1
Order By: Relevance
“…Nowadays, plant-based fermented beverages are one of the most important segments within the functional food sector [ 6 ]. It has been largely demonstrated that lactic acid fermentation improves sensory characteristics, nutritional quality, texture and safety of starch-containing vegetables including cereals [ 7 ]. Strong scientific evidence support the beneficial effects of lactic acid bacteria fermentation in cereal matrices by enhancing the content and bioavailability of phenolic compounds, γ-aminobutyric acid (GABA) and antioxidant, anti-hypertensive and anti-inflammatory activities [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, plant-based fermented beverages are one of the most important segments within the functional food sector [ 6 ]. It has been largely demonstrated that lactic acid fermentation improves sensory characteristics, nutritional quality, texture and safety of starch-containing vegetables including cereals [ 7 ]. Strong scientific evidence support the beneficial effects of lactic acid bacteria fermentation in cereal matrices by enhancing the content and bioavailability of phenolic compounds, γ-aminobutyric acid (GABA) and antioxidant, anti-hypertensive and anti-inflammatory activities [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The enzymatic activity is responsible for biopolymers degradation, leading to cell wall degradation (softening). LAB make the food easily digestible, decreasing the level of high-chain carbohydrates and some indigestible poly- and oligo-saccharides [ 56 ]. This is of great importance from the sensorial, physicochemical and dietary point of view, because carbohydrates digestibility is related to many human health issues [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…and Lactobacillus spp., for dairy products, but also the genera Pediococcus, Oenococcus, and Weissella play a pivotal role in plant-based fermented products (Wuyts et al, 2020). Leading approaches are used to improve the characteristics of these industrial bacteria (Hidalgo-Cantabrana et al, 2017;Bron et al, 2019), but the natural resources are also relevant to find novel strains with biotechnological applications (Bachtarzi et al, 2019;Petrova and Petro, 2020). Therefore, the same approaches can be used for the selection of the best LAB candidates to ferment residues from plant materials.…”
Section: Fermentation Processes Employing Labmentioning
confidence: 99%